EFFECT OF MIRROR THERAPY THROUGH FUNCTIONAL ACTIVITIES TO IMPROVE MOVEMENT AS CENTRAL POST-STROKE PAIN TREATMENT: A CASE REPORT - Wahyuni Ramadhani Suaib; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2022)
Background: Stroke patients generally have disorders related to decreased functionality, motor disturbances being the most common. One symptom of stroke is sudden weakness of one side of the body on the face, arms and legs. Central post-stroke pain is a condition of central neuropathic pain arising directly from lesions of the cerebrovascular central somatosensory nervous system. Mirror therapy is a non-pharmacological therapy in the form of imaging of the limbs, where a mirror medium is used to convey visual stimulation to the brain through observing body parts of patients who are not disabled while doing a series of movements. Mirror therapy helps in reducing disability in the limbs of stroke patients and as a treatment. for post-stroke central pain, thereby helping to improve functional limbs and shorten the rehabilitation period. Summary of case: A 54-year-old man with painful spastic left hand has been diagnosed with infarct stroke in the right thalamus 2 years ago. Mirror therapy has been done for two weeks, precisely six days per week with a duration about 30 minutes. Mirror therapy is done by using a mirror media that is placed on both arms and hands of the patient symmetrically and the patient observes the reflection of a healthy limb through flexion, extension, finger counts, and grasping objects. Visual Analogue Scale (VAS Score) is used to measure the level of pain before and after mirror therapy. After one month of mirror therapy the patient experienced an increase in motor function and decrease in pain scale. Conclusion: Mirror therapy is a promising non-pharmacological method in reducing disability and central pain after stroke. Keyword: Stroke, central post-stroke pain, mirror therapy.